A K ATP channel-dependent pathway within alpha cells regulates glucagon release from both rodent and human islets of Langerhans. - MacDonald, P; De Marinis, Y; Ramracheya, R; Salehi, A; Ma, X; Johnson, P; Cox, R; Eliasson, L; Rorsman, P (2007)
Glucagon, secreted from pancreatic islet alpha cells, stimulates gluconeogenesis and liver glycogen breakdown. The mechanism regulating glucagon release is debated, and variously attributed to neuronal control, paracrine control by neighbouring beta cells, or to an intrinsic glucose sensing by the alpha cells themselves. We examined hormone secretion and Ca(2+) responses of alpha and beta cells within intact rodent and human islets. Glucose-dependent suppression of glucagon release persisted when paracrine GABA or Zn(2+) signalling was blocked, but was reversed by low concentrations (1-20 muM) of the ATP-sensitive K(+) (KATP) channel opener diazoxide, which had no effect on insulin release or beta cell responses. This effect was prevented by the KATP channel blocker tolbutamide (100 muM). Higher diazoxide concentrations (>/=30 muM) decreased glucagon and insulin secretion, and alpha- and beta-cell Ca(2+) responses, in parallel. In the absence of glucose, tolbutamide at low concentrations (<1 muM) stimulated glucagon secretion, whereas high concentrations (>10 muM) were inhibitory. In the presence of a maximally inhibitory concentration of tolbutamide (0.5 mM), glucose had no additional suppressive effect. Downstream of the KATP channel, inhibition of voltage-gated Na(+) (TTX) and N-type Ca(2+) channels (omega-conotoxin), but not L-type Ca(2+) channels (nifedipine), prevented glucagon secretion. Both the N-type Ca(2+) channels and alpha-cell exocytosis were inactivated at depolarised membrane potentials. Rodent and human glucagon secretion is regulated by an alpha-cell KATP channel-dependent mechanism. We propose that elevated glucose reduces electrical activity and exocytosis via depolarisation-induced inactivation of ion channels involved in action potential firing and secretion.